Combustion Analysis of Thermal Barrier Coated Diesel Engine Using Fecl3 as Fuel Additive - Mohapatra, Debajit; P Jena, Shakti; Mishra, Ashutos; K Acharya, Saroj; K. Swain, Ranjan (International Journal of Engineering and Technology, 2018)
In this current study, combustion and emission parameters of a thermal barrier coated(TBC) compression ignition(CI) engine were studied. Ferric chloride (FeCl3) as fuel additive was mixed in diesel to enhance the combustion and emission characteristics of the engine. The results revealed that coated engine operated with FeCl3 mixed diesel increased the combustion duration with a reduction in ignition delay resulting in improved brake power. The maximum pressure rise occurs nearer to top dead centre in case of coated engine that to without TBC engine . The peak cylinder pressure reached to 53.5 bar for diesel as compared to 54.56 bar in case of FeCl3 added diesel in uncoated engine. While in case of coated engine the peak cylinder pressure reached 54.18 and 56 bar for diesel and FeCl3 mixed diesel respectively. The thermal barrier coating (TBC) enhanced the combustion characteristics, resulting efficient utilization of fuel leading to reduced engine emissions except nitric oxide emission.